EVALUASI RPS RUMPUN ILMU EKONOMI PADA PROGRAM STUDI PENDIDIKAN EKONOMI FKIP UNSRI - Siti Fatimah; Dewi Koryati; Dewi Pratita (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2020)
This study aims to determine how effective the Semester Learning Plan (RPS) for the economics course in the Economic Education Study Program. The evaluation model used in this research is the CIPP Evaluation Model. Determination of the effectiveness of a RPS that is used is seen from the level of student understanding of economic science material which is interrelated with one another under the clump of economics. This research is a type of qualitative researach that uses the CIPP model by evaluating each component of the context, input, process and product to reaach an agreement in compiling an effective RPS between lecturers who teach courses in the economics cluster with students as learners. Sources of research data are RPS and lecturers who are teaching courses under the economics cluster. Primary data collection uses observation instruments, while secondary data is obtained through documentation and interviews. The observation data obtained were then analyzed qualitatively. The results of the analysis of the CIPP model instrument from the context component are very effective, the input component is effective, the process component is effective and the product component is quite effective in the RPS for courses under the clump of economics to be used in learning activities